Efektivitas Penggunaan Kurikulum Darurat Covid-19 Pada Pembelajaran Bahasa Arab Di MTsN 3 Kota Palu - Titin Fatimah; Moh. Rall (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to find out how the Covid-19 Emergency Curriculum is used and the effectiveness of its use in learning Arabic. The research approach uses descriptive qualitative using observation, interview, and documentation techniques. The results of this study show that the use of the Covid-19 Emergency Curriculum at MTsN 3 Palu City is appropriate based on the curriculum concept that has been designed, the use of the Covid-19 Emergency Curriculum is carried out online and offline. Online learning is supported by E-Learning applications as learning media. And also the provision of learning modules for students who do learning offline; and the use of the Covid-19 Emergency Curriculum in learning Arabic can be said to be ineffective with a percentage of 60% of students experiencing complaints in the learning process, in the form of difficulties in understanding teaching material, as well as inadequate internet network access.